The Effectiveness of Differentiated Learning in Indonesian Language Subjects at Elementary Schools - Agus Riyanto; Gunarhadi Gunarhadi; Sukarno Sukarno (Papanda Publisher, 2026)
The COVID-19 pandemic exacerbated learning losses in literacy, necessitating effective pedagogical interventions. This study investigated differentiated instruction effectiveness within Indonesia's Merdeka Curriculum framework for sixth-grade Indonesian language education. A qualitative multiple-case study was conducted from March to May 2025 at two Sekolah Penggerak elementary schools in Central Java, Indonesia, involving 26 students and two teachers. Data collection employed document analysis of teaching modules, semi-structured interviews, and systematic classroom observations. Analysis followed the Miles and Huberman interactive model with triangulation to ensure credibility. Both teachers achieved